Green tea epigallocatechin gallate attenuate metabolic dysfunction-associated steatotic liver disease by regulation of pyroptosis - Jie Zhang; Shuangshuang Wang; Ting Zhang; Minghui Zi; Shuxiang Wang; Qiao Zhang (Lipids in Health and Disease)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) has become the most common chronic liver disease, with other fat-liver diseases potentially progressing to cirrhosis and hepatocellular carcinoma. Our study aimed to alleviate MASLD by EGCG inhibiting oxidative stress-mediated pyroptosis in zebrafish. Methods The one month old wild-type zebrafh larval (50 per group) and three months old adult male zebrafish (15 per group) were treated with high-fat diet (HFD) feeding (powdered egg yolk) following by treatment with 25 μM EGCG for 15 days. Indicators related to liver damage, oxidative stress, inflammation, pyroptosis and aging were assessed using Oil Red O staining, H&E staining, commercial assay kits, enzyme-linked immunosorbent assay (ELISA) kits, and Western blot analysis. Results The results suggest that EGCG significantly reduced fatness, severe lipid deposition, triglyceride (TG), total cholesterol (TC) and free fatty acid (FFA) levels (p < 0.05). EGCG markedly reduced serum ALT, AST and ameliorated liver injury in zebrafish (p < 0.05). EGCG also showed an antioxidant effect by reducing reactive oxygen species (ROS) production malondialdehyde (MDA) and increasing superoxide dismutase (SOD) levels (p < 0.05). Moreover, EGCG obviously down-regulated the pro-inflammatory factors like tumor necrosis factor-a (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and interleukin-18 (IL-18) levels (p < 0.05). EGCG indicated a significant upregulation involved in pyroptosis pathway, such as nuclear factor erythroid 2-related factor 2 (NRF2) and downregulated the expressions of nuclear factor-κB (NF-κB), NOD-like receptor thermal protein domain associated protein 3 (NLRP3), apoptosis-associated speck-like protein containing a CARD (ASC), cysteinyl aspartate specific proteinase-1 (caspase-1), as well as gasdermin D (GSDMD) (p < 0.01). Moreover, EGCG significantly improved aging-related markers induced by a HFD, including the level of senescence-associated β-Galactosidase (SA β-Gal) and expression of p53, p16, and p21 (p < 0.05), while ameliorating liver function in zebrafish. Conclusions These results suggest that EGCG may attenuate MASLD in larval and adult zebrafish induced by 15 consecutive days HFD, which is potentially mediated by modulating the Nrf2/NF-κB/NLRP3 signaling pathway which relieve pyroptosis.